Neutrophil-Lymphocyte ratio as a predictor of haemorrhagic stroke outcomes - Rohmania Setiarini; Subagya; Ismail Setyopranoto (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Haemorrhagic stroke causes high disability and mortality. Moreover, the prevalence is increasing. There is evidence of the involvement of the inflammatory process in haemorrhagic strokes. The neutrophil-lymphocyte ratio (NLR) is a strong and easily assessed marker of inflammation. Objective: This study aims to determine the NLR during hospital admission as a predictor of neurological deterioration in acute haemorrhagic strokes.Methods: This study was a prospective cohort study. The subjects were acute haemorrhagic stroke patients treated at the Stroke Unit of the RSUP Dr. Sardjito between March and November 2018. The demographic and laboratory test data, including NLR and National Institutes of Health Stroke Scale (NIHSS) measurement upon admission, were investigated. Logistic regression was performed to identify independent risk factors of neurological deterioration.Results: A total of 65 haemorrhagic stroke patients were included in this study. There were 21 subjects experiencing neurological deterioration, and 44 subjects did not. In bivariate analysis, there was a significant association between hyperglycaemia and neurological deterioration (RR=3.073; 95%CI=1.772-5.329; p=0.011). Glasgow Coma Scale (GCS) at admission was significantly associated with neurological deterioration (RR=2.732; 95%CI=1.455-5.131; p=0.006) as well as the NLR (RR=3.750; 95%CI=1.229-9.4441; p=0.005). The logistic regression results demonstrated that the variables that independently influenced neurological deterioration were NLR (RR= 4.424; 95%CI=1.196-16.369; p=0.026) and GCS (RR=7.461; 95%CI=1.711-32.526; p=0.007).Conclusion: High NLR can predict deterioration in acute haemorrhagic stroke.